2021
DOI: 10.1021/acsinfecdis.0c00897
|View full text |Cite
|
Sign up to set email alerts
|

Pyochelin Biosynthetic Metabolites Bind Iron and Promote Growth in Pseudomonads Demonstrating Siderophore-like Activity

Abstract: Pseudomonads employ several strategies to sequester iron vital for their survival including the use of siderophores such as pyoverdine and pyochelin. Similar in structure but significantly less studied are pyochelin biosynthetic byproducts, dihydroaeruginoic acid, aeruginoic acid, aeruginaldehyde (IQS), and aeruginol, along with two other structurally related molecules, aerugine and pyonitrins A−D, which have all been isolated from numerous Pseudomonad extracts. Because of the analogous substructure of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
3
23
0
Order By: Relevance
“…This feature was annotated as aeruginoic acid ( 3 ), which is a shunt product in the pyochelin biosynthesis pathway observed in Pseudomonas and Burkholderia spp. 70 , 71 . Aeruginoic acid is the oxidized form of aeruginaldehyde (also known as the integrated quorum sensing signal, or IQS), which has been proposed as a “fourth QS molecule” in P. aeruginosa , although this claim has been disputed 72 , 73 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This feature was annotated as aeruginoic acid ( 3 ), which is a shunt product in the pyochelin biosynthesis pathway observed in Pseudomonas and Burkholderia spp. 70 , 71 . Aeruginoic acid is the oxidized form of aeruginaldehyde (also known as the integrated quorum sensing signal, or IQS), which has been proposed as a “fourth QS molecule” in P. aeruginosa , although this claim has been disputed 72 , 73 .…”
Section: Resultsmentioning
confidence: 99%
“…Aerugine has been previously isolated from Pseudomonas fluorescens and exhibits selective antifungal activity 76 . Recent work by Kaplan et al has indicated that aeruginaldehyde, aerugine, and aeruginoic acid have iron-binding activity with aeruginoic acid binding to Fe 3+ with a 1:1 ratio, aeruginaldehyde binding with a 2:1 ratio, and aerugine binding with a 3:1 ratio 71 . Unlike pyochelin, aeruginoic acid has a specific affinity for iron compared to other biologically relevant metals 71 .…”
Section: Resultsmentioning
confidence: 99%
“…This feature was annotated as aeruginoic acid (3), which is a shunt product in the pyochelin biosynthesis pathway observed in Pseudomonas and Burkholderia spp. 70,71 . Aeruginoic acid is the oxidized form of aeruginaldehyde (also known as the integrated quorum sensing signal, or IQS), which has been proposed as a "fourth QS molecule" in P. aeruginosa, although this claim is disputed 72,73 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent work by Kaplan et. al has indicated that aeruginaldehyde, aerugine, and aeruginoic acid all have iron-binding activity with aeruginoic acid binding to Fe 3+ with a 1:1 ratio, aeruginaldehyde binding with a 2:1 ratio, and aerugine binding with a 3:1 ratio 71 . Unlike pyochelin, aeruginoic acid has a speci c a nity for iron compared to other biologically relevant metals 71 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation